Simultaneous Provision of Flexible Ramping Product and Demand Relief by Interruptible Loads Considering Economic Incentives - Jiahua Hu; Fushuan Wen; Ke Wang; Yuchun Huang; Md. Abdus Salam (Energies, 2017)
To cope with the net load variability in real time, sufficient ramp capability from controllable resources is required. To address the issue of insufficient ramp capacity in real time operations, flexible ramping products (FRPs) have been adopted by some Independent System Operators (ISOs) in the USA as a new market design. The inherent variability and uncertainty caused by renewable energy sources (RESs) call for new FRP providers apart from conventional generating units. The so-called interruptible load (IL) has proved to be useful in maintaining the supply-demand balance by providing demand relief and can be a viable FRP provider in practice. Given this background, this work presents a stochastic real-time unit commitment model considering ramp requirement and simultaneous provision of IL for FRP and demand relief. Load serving entities (LSEs) are included in the proposed model and act as mediators between the ISO and multiple ILs. In particular, incentive compatible contracts are designed to encourage customers to reveal their true outage costs. Case studies indicate both the system and LSEs can benefit by employing the proposed method and ILs can gain the highest profits by signing up a favorable contract.